2004
DOI: 10.1002/nau.20005
|View full text |Cite
|
Sign up to set email alerts
|

Variation in urological practice amongst spinal injuries units in the UK and Eire

Abstract: The variation in urological practice amongst SIU in the UK and Eire is considerable. This finding supports the need for an increase in the level of collaboration and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…17 However, there is little data relating to the value of sequential urodynamic testing, thus there is currently a wide variability in the management strategies amongst specialists. 10,11 Nosseir and colleagues retrospectively investigated the long-term results of 80 SCI patients managed at their institution with a strictly urodynamic-based treatment regime and determined that physiologic changes in bladder function can occur in the absence of changes in overall symptoms, thus they recommended annual urodynamic testing in patients with detrusor overactivity. 18 With the hypothesis that annual UDS is unnecessary, we retrospectively assessed our population of SCI patients managed with CIC to report the efficacy of a surveillance regime based on annual renal tract ultrasonography without annual UDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, there is little data relating to the value of sequential urodynamic testing, thus there is currently a wide variability in the management strategies amongst specialists. 10,11 Nosseir and colleagues retrospectively investigated the long-term results of 80 SCI patients managed at their institution with a strictly urodynamic-based treatment regime and determined that physiologic changes in bladder function can occur in the absence of changes in overall symptoms, thus they recommended annual urodynamic testing in patients with detrusor overactivity. 18 With the hypothesis that annual UDS is unnecessary, we retrospectively assessed our population of SCI patients managed with CIC to report the efficacy of a surveillance regime based on annual renal tract ultrasonography without annual UDS.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, data relating to the value of sequential ultrasonography or urodynamic testing are scarce, thus there is great variability in urologic management of these patients in the United States and around the world. [9][10][11] A 2002 survey of 160 US Society of Urodynamics, Female Pelvic Medicine & Urogenital Reconstruction (SUFU) members by Razda and colleagues revealed that 80% of respondents performed annual ultrasound for upper tract surveillance. Up to 65% of respondents performed urodynamics annually or every other year for lower tract monitoring.…”
mentioning
confidence: 99%
“…7 In addition, the current long-term management was compared with the published guidelines for compliance. The EAU guidelines 4 are not SCI specific but include SCI-associated NLUTD.…”
Section: Discussionmentioning
confidence: 99%
“…We sent the same questionnaire as in the earlier study 7 to the consultant urologists at the 12 SCI centres in the United Kingdom and Ireland (Appendix). If the filled questionnaire was not received after 1 month, a second questionnaire was sent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation